NEW WAY TO CREATE HIGH-SPEED LCD’S BASED ON THE USE OF MODIFIED NANOMATERIALS - V. I. Lapanik; A. P. Lugovsky; S. N. Timofeev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The object of research is liquid crystal materials of the nematic and smectic types containing modified nanoparticles of detonation diamonds, partially reduced graphene and nanoclay. The purpose of the work is the development of new functional materials with improved physicochemical and electro-optical characteristics. During the study, methods for chemical modification of the surface of nanoparticles were developed; the mesomorphic, dielectric and electro-optical properties of nematic and ferroelectric compositions, doped with modified nanomaterials are studied. It has been established that the effect of modified nanodiamonds on the mesomorphic, dielectric, and electro-optical properties of liquid crystals is large and depends on the size of these particles and the type of grafted functional groups. Small-sized diamond nanoparticles do not significantly affect the properties of liquid crystals. At the same time, conglomerates based on nanodiamonds with a diameter of about 50–100 nm can increase or decrease the dielectric anisotropy and the response time of liquid crystals by 1,5–2,5 times, depending on the polarity of the functional groups. It has been experimentally shown that the addition of a small amount of graphene flakes to nematic and ferroelectric liquid crystals can significantly improve the electro-optical response time (up to 2 times depending on concentration). There is a decrease in threshold (by 7–30 %) and saturation voltages (by 11–31 %). For ferroelectric liquid crystals, the addition of graphene leads to an increase in the tilt angle and a spontaneous polarization.